ELUCIDATION TERRITORIAL REGULATION EFFECT ON INDUSTRY AND TRADE OF EMPLOYERS RESPONSIBILITY TO PAY SIUP RETRIBUTION - Dody Hermana (Jurnal Ilmiah Ekonomi Bisnis, 2009)
The objective of this research is to analyze the influence of extension on responsibility of businessperson and domestic income, and to analyze the impact of responsibility of local businesspersons on domestic income. Data were collected through interview, observation, and documentation study. Path analysis was used in this research. Results of this research showed that extension program of Regional Regulation was perceived well organized, responsibility of businesspersons in paying regional tax was high, and there was significant increase in domestic income. It was also found that Regional Regulation extension program has no significant effect on both the rate of businessperson’s responsibility and domestic income in Kabupaten Cirebon. In addition, effectiveness of Regional Regulation extension program depends heavily on knowledge capacity of extension officers as well as their attitudes in delivering information through the program. Implications of this research are that persuasive approaches, honesty, and transparencies of tax officers are required in collecting regional trade license tax from regional taxpayers. These, in turn, will result in a better sympathetic and responsibility of business community.Key words: Domestic Industrial and Trade Regulation Extension Program; businesspersons; domestic income; taxpayer responsibility.